2017
DOI: 10.1159/000478752
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Oxidative Stress by 17 β-Estradiol and Genistein in Human Hepatic Cell Lines In Vitro

Abstract: Background/Aims: estrogens and phytoestrogens exert hepatoprotection through mechanisms not clearly examined yet. Here, we investigated the protective effects exerted by 17β-estradiol and genistein against oxidative stress in hepatocytes and hepatic stellate cells (HSCs) and the involvement of specific receptors and the intracellular signalling. Methods: Huh7.5 and LX-2, alone or in co-culture with Huh7.5, were treated with 17β-estradiol and genistein alone or in the presence of menadione and of estrogen recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 45 publications
1
40
0
Order By: Relevance
“…Gloria Gutiérrez-Venegas et al revealed that genistein was able to hinder the LPS-induced inflammatory response in H9c2 cells and decrease damage in myocardial cells due to LPS exposure [20]. Surico D et al reported that genistein and 17β-estradiol counteract the effects of peroxidation by an intracellular signal related to Akt and p38 MAPK and through the involvement of ERs and GPER [21]. In addition, Catmull S et al proposed that dietary genistein rescued reduced basal chloride in the diabetic Jejunum via sex-dependent mechanisms [22].…”
Section: Discussionmentioning
confidence: 99%
“…Gloria Gutiérrez-Venegas et al revealed that genistein was able to hinder the LPS-induced inflammatory response in H9c2 cells and decrease damage in myocardial cells due to LPS exposure [20]. Surico D et al reported that genistein and 17β-estradiol counteract the effects of peroxidation by an intracellular signal related to Akt and p38 MAPK and through the involvement of ERs and GPER [21]. In addition, Catmull S et al proposed that dietary genistein rescued reduced basal chloride in the diabetic Jejunum via sex-dependent mechanisms [22].…”
Section: Discussionmentioning
confidence: 99%
“…Cell viability was examined by using the 1% 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl tetrazolium bromide (MTT; Life Technologies, Italia, Monza, Italy) dye, as previously described [ 19 , 22 , 23 ] both in pre-adipocytes and in white adipocytes (treated with DM) and in brown adipocytes (treated with DM supplemented with 1 nM T3). Pre-adipocytes/adipocytes were treated in physiological and peroxidative conditions with adiponectin (100 µM; Sigma) and genistein at different doses (10 pM, 1 µM, 50 µM and 200 µM; Sigma) for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial membrane potential measurement was performed with JC-1 assay as previously described for cell viability. After stimulation, the treatment medium was removed and cells were incubated with 5,51,6,61-tetrachloro-1,11,3,31 tetraethylbenzimidazolyl carbocyanine iodide (JC-1) 1X diluted in Assay Buffer 1X for 15 min at 37 °C, following the manufacturer’s instruction and as previously performed (Invitrogen, Life Technologies Europe BV, Monza, Italy) [ 19 , 22 , 23 ]. After incubation, the cells were washed twice with Assay Buffer 1× and then the mitochondrial membrane potential was determined by measuring the red (excitation 550 nm/emission 600 nm) and green (excitation 485 nm/emission 535 nm) fluorescence through a spectrometer (BS1000 Spectra Count).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations